Implementation of Discharge Planning Using Leaflet Media for Coronary Heart Disease Patients in Indonesian Hospital - Nuraeni, Ani; Nufus, Tazqiatun (Journal of Health, Medicine and Nursing, 2025)
Coronary Heart Disease is one of the leading causes of illness and death worldwide. Patients with coronary heart disease often experience recurring events and require effective discharge planning to ensure continuity of care and prevent further complications. Proper discharge planning can enhance patients' understanding of their condition management and reduce the likelihood of rehospitalization. This study aims to evaluate the effectiveness of discharge planning in improving patient adherence to treatment and enhancing quality of life to reduce readmission rates among patients with Coronary Heart Disease (CHD). The research method employed is a descriptive case study. The study sample consists of CHD patients hospitalized in a hospital setting. During their hospital stay, patients received structured discharge planning, including health education, follow-up plans, and coordination with healthcare services. The results of implementing the discharge planning intervention over 3 days showed differences in knowledge levels before and after the intervention. Following education, improvements were observed in patients' knowledge regarding implementing care programs, taking actions to mitigate risks, and engaging in daily activities to achieve health goals.